ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN 102 PEMBIAYAAN MURABAHAH PADA BAITUL MAAL WATAMWIL NURUL ISLAM BATAM - JUAN, RAJA EKA; OMPUSUNGGU, HERMAYA (SCIENTIA JOURNAL, 2020)
This research was conducted at BMT Nurul Islam Batam with the title: Analysis of the Application of Financial Accounting Standards Statement 102 Murabaha Financing at Baitul Maal Watamwil Nurul Islam Batam. This study aims to determine the suitability of the application of murabaha accounting at BMT Nurul Islam Batam with the Financial Accounting Standards Statement 102 murabaha financing. This type of research uses a qualitative approach. The data collection method uses interviews and documentation, which compares the object of research with the concept of comparison To determine the appropriateness of murabaha accounting practices by BMT Nurul Islam Batam, the standard rules contained in PSAK No. 102 murabaha financing. The results of the study can be seen that the accounting treatment murabaha on BMT Nurul Islam Batam relating to recognition and measurement, presentation and disclosure has been prepared in accordance with PSAK No. 102 murabaha financing.